Impelementation of Information Technology Service Management at Data And Information System Center of XYZ University - Irfandhi, Kornelius; Indrawati, Ariani; Alexandra, Dwykie; Wanandi, Krisantus; Harisky, Yanuari; Liawatimena, Suryadiputra (ComTech: Computer, Mathematics and Engineering Applications, 2016)
Information Technology (IT) is increasingly progressing. Nowadays, the success of a business of the organization/company is highly dependent on the IT infrastructure used. Therefore, organizations/companies have to manage their IT service to be optimal to their customers. Looking at this matter and the increasing dynamics of XYZ University, then Data and Information System Center (Pusdatin) - an IT provider of XYZ University began implementing IT Service Management (ITSM) from 2013 using the latest version of Information Technology Infrastructure Library (ITIL), namely ITIL v3 as a framework for implementing ITSM in its business processes. However, along the way, there are still some problems happen in Pusdatin in order that ITSM can actually support and align with the objectives of XYZ University. Through this paper, the authors want to explain how the implementation of ITSM at Pusdatin, identify the problems related to the implementation of ITSM, and provide the solutions for each problem. The methods used are direct observation to Pusdatin, conductan interview with the Head of Pusdatin and Staff of Pusdatin, and also perform a literature review of books and papers that discuss about ITIL. The result of this research is that ITSM process of Pusdatin generally works quite well but there are still some shortcomings because ITSM is not 100% implemented in all areas.